Impact of a deletion of the full-length and short isoform of p75NTR on cholinergic innervation and the population of postmitotic doublecortin positive cells in the dentate gyrus - Poser, Robert; Dokter, Martin; von Bohlen und Halbach, Viola; Berger, Stefan M.; Busch, Ruben; Baldus, Marian; Unsicker, Klaus; von Bohlen und Halbach, Oliver (Frontiers in Neuroanatomy, 2015)
Analyses of mice carrying a deletion of the pan-neurotrophin receptor p75NTR have allowed identifying p75NTR as an important structural regulator of the hippocampus. Most of the previous analyses were done using p75NTRExIII knockout mice which still express the short isoform of p75NTR. To scrutinize the role of p75NTR in the hippocampus, we analyzed adult and aged p75NTRExIV knockout mice, in which both, the short and the full-length isoform are deleted. Deletion of these isoforms induced morphological alterations in the adult dentate gyrus (DG), leading to an increase in the thickness of the molecular and granular layer. Based on these observations, we next determined the morphological substrates that might contribute to this phenotype. The cholinergic innervation of the molecular and granular layer of the DG was found to be significantly increased in the knockout mice. Furthermore, adult neurogenesis in the DG was found to be significantly altered with increased numbers of doublecortin (DCX) positive cells and reduced numbers of apoptotic cells in p75NTRExIV knockout mice. However, cell proliferation as measured by phosphohiston H3 (PH3) positive cell numbers was not affected. These morphological alterations (number of DCX-positive cells and increased cholinergic fiber densities) as well as reduced cell death in the DG are likely to contribute to the observed thickening of the granular layer in p75NTRExIV knockout mice. In addition, Sholl-analysis of DCX-positive neurons revealed a higher dendritic complexity and could thus be a possible morphological correlate for the increased thickness of the molecular layer in p75NTR deficient animals. Our data clearly demonstrate that deletion of both, the short and the full-length isoform of p75NTR affects DG morphology, due to alterations of the cholinergic system and an imbalance between neurogenesis and programmed cell death within the subgranular zone.